The responsibility to protect the promise of stopping mass atrocities in our time - Genser, Jared; Cotler, I. (Irwin), 1940- (New York ; Oxford : Oxford University Press, 2011)
'The Responsibility to Protect' provides a comprehensive view on how this contemporary principle has developed and analyzes how to best apply it to current humanitarian crises.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Humanitarian intervention; Atrocities -- Prevention; Genocide -- Prevention